Variation of thermal parameters in two different color morphs of a diurnal poison toad, Melanophryniscus rubriventris (Anura: Bufonidae) - Sanabria, Eduardo Alfredo (2014)
We study the variation in thermal parameters in two contrasting populations Yungas Redbelly Toads (Melanophryniscus rubriventris) with different discrete color phenotypes comparing field body temperatures, critical thermal maximum and heating rates. We found significant differences in field body temperatures of the different morphs. Temperatures were higher in toads with a high extent of dorsal melanization. No variation was registered in operative temperatures between the study locations at the moment of capture and processing. Critical thermal maximum of toads was positively related with the extent of dorsal melanization. Furthermore, we founded significant differences in heating rates between morphs, where individuals with a high extent of dorsal melanization showed greater heating rates than toads with lower dorsal melanization.The color pattern-thermal parameter relationship observed may influence the activity patterns and body size of individuals. Body temperature is a modulator of physiological and behavioral functions in amphibians, influencing daily and seasonal activity, locomotor performance, digestion rate and growth rate. It is possible that some growth constraints may arise due to the relationship of colorpattern-metabolism allowing different morphs to attain similar sizes at different locations instead of body-size clines.